Pengaruh Produk Pembiayaan Mudharabah dan Layanan Digital terhadap Keputusan Nasabah pada BTPN Syariah MMS Panjang - Rosmiati, Heni; Khulsum, Umi; Azizah Zuhriyah, Nur; Utami, Pertiwi (Masoem University, 2025)
This study's objective is to investigate whether there is an influence of mudharabah financing products and digital services on customer decisions at BTPN Syariah MMS Panjang in the TUNA era. This type of research is quantitative research. The sampling technique in this study is Simple Random Sampling. Data collection by distributing questionnaires through the Google form application with the number of samples used in this study was 95 respondents from BTPN Syariah MMS Panjang customers. The software used to analyze the data uses the assistance of the Smart PLS 4.1 application. Data analysis such as reliability testing and validity testing using the outer model. While testing the relationship between the coefficient of determination and hypothesis testing using the inner model. The results of the study show that partially based on the structural model test, it has an R² (Coefficient of Determination) value, it can be seen that the R-square value on the Mudharabah Financing variable (X1), and Digital Services (X2), on the Customer Decision variable (Y) has an effect together or simultaneously with a value of 0.359. Thus, it can be concluded that 36% of Customer Decisions are explained by the Mudharabah Financing and Digital Services variables. Based on the regression model, the path coefficient value is 0.513, t-statistic = 5.038, P-value = 0.000 <0.05 for the mudharabah financing variable, and the path coefficient value is 0.110, t-statistic = 1.267, P-value = 0.114> 0.05 for the digital services variable. Both variables have a positive and significant influence on the decision to become a customer at BTPN Syariah MMS Panjang Bandar Lampung